Surface Accessibility with Spatial Analysis During Fire Extinguishing Procedures: Example on the Island of Vis - Kruno Lepoglavec; Josip Žaček; Hrvoje Nevečerel; Ante Seletković; Zdravko Pandur; Marin Bačić (South-East European Forestry, 2017)
Background and Purpose: The existing public and forest transport infrastructure (truck forest roads) are permanent objects used when passing through forests. They also serve as a firefighter belt and provide direct access to firefighting vehicles, or are used as the starting point where firefighting teams extinguish fires or move toward remote fires. The paper identifies the existing fire road network (including public roads, forest roads, non-classified roads and fire roads) for access of firefighting vehicles during fire extinguishing interventions. Material and Methods: An analysis of the intervention rate was conducted on a dispersive sample (35 positions) from two volunteer fire associations (VFA) on the island of Vis. Also, an analysis of the surface availability to fire vehicles concerning the time of departure from the fire station was conducted, as well as the comparison with the Standard time of intervention defined by the regulations on fire department organization in the Republic of Croatia. Results: For each simulated fire location for intervention of two existing volunteer fire associations: VFA Komiža and VFA Vis, results show that for a few fire locations, despite a smaller distance from the VFA Komiža, a quicker intervention is possible from the VFA Vis (locations 4, 5 and 14), and vice versa (locations 21, 22 and 25). With the use of a New Service Area, tool intervention times regarding different areas were calculated. Intervention times were divided into intervals: <5 min, 5–10 min, 10–15 min, 15–25 min and >25 min. The last two categories of area are beyond reach for firefighters within the Standard time of intervention (15 min) and together they comprise to 27.88% of the total research area. Conclusions: The results of Closest Facility tool indicate that for the simulated fire position the best/fastest route is not always the shortest one, because of a significant effect of the structural elements of each road, the state of the road and the longitudinal slope of the road itself. One of the possible approaches to gain access to the area for fire-fighting, as well as to prioritize fire roads regarding maintenance/reconstruction is to improve road conditions, and thus increase the average driving speed.